(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Fluoride removal from aqueous solution was investigated using the chemical coagulation-flocculation by alum in reason of the efficiency and the simplicity of the process. Preliminary experiments were carried out to study the effect of some operating parameters such as: pH, initial fluoride concentration, coagulant dose, adjuvant coagulation dose, flocculent dose and settling time. Obtained experimental results showed that the treatment of fluoride by alum coagulation causes acidification of the solution. The effect of the initial pH solution on fluoride removal is negligible. Experimental results proved that coagulation process is effective in waters with low or medium levels of fluoride. Defluoridation rate was seen to increase with increasing coagulant and adjuvant coagulation doses. Optimal flocculent dose and optimal settling time were found 4.2 mg L-1 of FABI and 60 min respectively. Subsequently, experimental design methodology using two-level full factorial design was applied to optimize the defluoridation by coagulation-flocculation. Therefore, four operating parameters which are supposed to affect the removal efficiency were chosen: initial fluoride concentration, coagulant dose, coagulation adjuvant dose and settling time. From the statistical analysis, it is inferred that the four studied parameters have an influence on the fluoride removal. In fact, initial fluoride concentration has a positive effect unlike coagulant dose, coagulation adjuvant dose and settling time. Experiment tests were performed to evaluate the efficiency of coagulation-flocculation process for south Tunisian brackish water with high fluoride concentration. The obtained results showed that fluoride removal reached 59%.